INTERPRETATION OF GAMMA RAY VALUE BASED ON OUTCROP DATA IN SIMPENAN AREA, REGENCY OF SUKABUMI - Firmansyah, Yusi; Ganjar Gani, Reza Moh.; Nurdrajat, Aji (Journal of Geological Sciences and Applied Geology, 2018)
Natural radiation is the radiation that exists in nature in the form of cosmic radiation and the radiation is derived from the radioactive material present in the earth's crust (IAEA, 2003). This radionuclide is present in almost any material such as earth's crust, rocks, soil layers, seawater, building materials and human bodies of different levels. Generally these radiometric traces of an outcrop depend on the original rock that can be seen from petrology. The geological condition of Ciletuh in Sukabumi Regency is quite complex, seen from the structure of rocks, the characteristics of rocks, stratigraphy and also the landscape, thus making the area of Ciletuh interesting enough to serve as the location of research research in the field of Geology. Landslide disaster is one of the most common disasters in Indonesia. Based on data from the National Disaster Management Agency (BNPB) within the period of 2011-2014 there were 493 cases of landslides recorded in Indonesia. The potential of disaster and landslide vulnerability is a threat to the people of the Simpenan area, Sukabumi Regency which has geographical condition that is prone to landslide disaster. The purpose of this research is to know the distribution of Gamma Ray value in exposed rock and to see the relation of Gamma Ray value distribution with landslide prone area in research area. In the field observation, the lithology was 70% dominated by polymic breccia as well as 30% sandstone and claystone. The mean overall gamma ray value in the study area was 0.036 μSv / h. The landslide-prone areas in the study area have high gamma ray values and are located in areas with steep to steep slopes (8-35 °) where the reliefs are controlled by claystone lithology which has high potassium and thorium contents and is susceptible to weathering, erosion and prone to landslides. Keywords: Gamma Ray, landslide, Stratigraphy